1999
DOI: 10.1063/1.123717
|View full text |Cite
|
Sign up to set email alerts
|

Role of peripheral vacuum regions in the control of the electron cyclotron resonance plasma uniformity

Abstract: Spatial measurements of the ion saturation current density indicate stable vacuum regions in a periphery of electron cyclotron resonance (ECR) plasma. The vacuum regions have a possibility to contribute to plasma uniformity by behaving as a waveguide for the incident electromagnetic waves. Mode conversion of electromagnetic waves with long wavelength to the right circular polarized wave was observed experimentally at a certain radial position. Furthermore, microwave propagation in a partially filled plasma cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Ueda et al investigated microwave propagation in an ECR reactor by considering plasma with an outer vacuum region whose diameter is large compared with the earlier works. 16,17) They found that the vacuum region behaved as a waveguide and mode transformation into extraordinary or electrostatic wave occurred in the peripheral vacuum region. They indicated that upper hybrid resonance by the extraordinary wave played an important role in uniform plasma generation.…”
Section: (3) Low Wall Damagementioning
confidence: 99%
“…Ueda et al investigated microwave propagation in an ECR reactor by considering plasma with an outer vacuum region whose diameter is large compared with the earlier works. 16,17) They found that the vacuum region behaved as a waveguide and mode transformation into extraordinary or electrostatic wave occurred in the peripheral vacuum region. They indicated that upper hybrid resonance by the extraordinary wave played an important role in uniform plasma generation.…”
Section: (3) Low Wall Damagementioning
confidence: 99%
“…Over the past few decades, a considerable number of studies have focused on the whistler wave for weakly magnetized plasmas (ω pe /ω ce > 1) [13][14][15][16][17][18][19] because the wave has right-handed polarization and is efficiently absorbed near the ECR point, where ω pe /2π and ω ce /2π are the electron-plasma and electron-cyclotron frequencies, respectively. On the other hand, wave propagation and absorption under the condition of ω pe /ω ce < 1 have been investigated recently to produce uniform plasmas [20,21], in which a left-hand polarized wave (LHPW) is locally absorbed near the ECR point in inhomogeneously magnetized plasmas. To explain the unexpected absorption of the LHPW, which is not considered to be related to ECR, polarization reversal from the LHPW to a right-hand polarized wave (RHPW) was suggested for m = −1 mode by theoretical studies including the effects of radial boundaries and finite electron temperature [22].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported in the field of thermonuclear fusion that ECR is effective in the formation of local-confining potential [1,2], electron cyclotron current drive [3], suppression of disruption in a tokamak [4], and so on. In the field of processing plasma, on the other hand, it was reported that ECR is useful for the production of plasmas with high density, large diameter, and uniformity [5,6].Propagation and absorption of high frequency electromagnetic waves in plasmas have basically been significant research subjects since they play important roles in pursuing the above-mentioned applications. A right-hand polarized wave (RHPW) is straightforwardly accepted to be absorbed near the ECR point and its associated investigations have been performed for a long time [7,8], while a left-hand polarized wave (LHPW) was believed not to be related to ECR.…”
mentioning
confidence: 98%
“…It was reported in the field of thermonuclear fusion that ECR is effective in the formation of local-confining potential [1,2], electron cyclotron current drive [3], suppression of disruption in a tokamak [4], and so on. In the field of processing plasma, on the other hand, it was reported that ECR is useful for the production of plasmas with high density, large diameter, and uniformity [5,6].…”
mentioning
confidence: 99%